Low-carbohydrate diet - application in the treatment of type 2 diabetes - review - Justyna Woźniak; Karol Womperski; Julia Szymonik; Sebastian Szopa; Jagoda Elias (Nicolaus Copernicus University in Toruń, 2024)
Introduction: A very low carbohydrate diet called the ketogenic diet has been shown to be effective in the management of drug-resistant epilepsy. In the recent years it has been studied as a potential remedy for conditions such as insulin resistance, type 2 diabetes, obesity, cardiovascular diseases as well as various psychological disorders including drug-resistant depression and schizophrenia. This approach seems to be promising in managing abovementioned issues given a sufficient amount of commitment. There is an abundance of papers looking into the said diet yet not many of them seem to have been well deigned and carried out. Methods and materials: A review of chosen literature from PubMed database, GoogleScholar database between the years 2000-2024 was carried out using the following keywords: "low-carbohydrate", low-carb", "low carbohydrate diet", "low-carb diet", "type 2 diabetes", "insulin", "insulin resistance", "obesity". Aim of study: Review of the current knowledge on the influence of the therapeutic carbohydrate restriction on health, especially type 2 diabetes. Results: The introduction of the low-carbohydrate diet may have a beneficial influence on metabolism-related diseases. There is quite strong evidence proving it help with the management of type 2 diabetes and limit the amount of medication necessary to manage the disease as well as lower one's body fat and blood pressure. It is however not an intervention without its limitations. Conclusions: Low carbohydrate diets seem to be safe and effective in the treatment of Type 2 diabetes. Further large-scale, randomized, well-designed studies with clearly set guidelines as to what constitutes a low-carbohydrate intervention using high-quality protein and fat sources are necessary to determine the efficacy and safety of the carbohydrate restriction in the long term.